Stem cell therapy for reconstruction of alveolar cleft and trauma defects in adults: A randomized controlled, clinical trial. (28th June 2017) - Bajestan, Mona N.; Rajan, Archana; Edwards, Sean P.; Aronovich, Sharon; Cevidanes, Lucia H. S.; Polymeri, Angeliki; Travan, Suncica; Kaigler, Darnell
Abstract: Background: Stem cell therapy with bone marrow‐derived mesenchymal stem cells is a promising tissue engineering strategy to promote regeneration of craniofacial bone. Purpose: To determine whether cell therapy with ex vivo expanded stem cell populations would be safe and efficacious in the regeneration of large alveolar defects in patients with a history of cleft palate or craniofacial trauma. Materials and Methods: Eighteen patients (10 patients with traumatic injury and 8 patients with cleft palate) presenting with missing teeth associated with horizontal alveolar bone deficiencies were included in this randomized controlled clinical trial. Patients were randomized to receive either conventional autogenous block grafts or stem cell therapy. After a healing period of 4 months the treated sites were re‐entered and the bone width re‐assessed prior to implant placement. Implant stability was evaluated through torque testing of the implant upon insertion and at 6 months postloading. Results: The mean gain in bone width was 1.5 ± 1.5 mm in the stem cell therapy group and 3.3 ± 1.4 mm in the control group. Overall, bone gain was higher in trauma patients as compared to patients with cleft palate, for both the control and the stem cell therapy groups. Most postoperative complications were wound dehiscences and incision line openings. Implants were placed successfully in 5 out of 10 patients in the stem cell therapy group and in all 8 patients in the control group. One implant from the control/cleft palate group failed before loading, while the rest of the implants were loaded successfully and remained stable at 6 months. The patients who did not receive implants were re‐treated with autogenous block bone graft. Conclusion: The ability of stem cells to treat large alveolar defects is safe, yet, their ability to completely reconstitute large alveolar defects is limited. This approach requires further optimization to meet the outcomes seen using current methods to treat large defects, particularly those resultant of cleft palate.